Pierwsze efekty integracji z Unią Europejską w sektorze rolnym - Mickiewicz, Paweł (First Effects of the Integration with the European Union in Agriculture Sector, 2005)
The paper presents effects of the first months of the integration for Polish agriculture and possibilities of farmer development for the next few years. Data used in this elaboration have been gathered from the Agency of Restructuring and Modernization of Agriculture and the Ministry of Agriculture. Additionally some investigations with farmers have been made.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 92-96